Role of the National Human Rights Commission for the Protection of Human Rights in Nepal - Giri, Saroj Kumar (Dristikon: A Multidisciplinary Journal, 2022)
The article aims to analyze the role of the National Human Rights Commission (NHRC) in the protection and promotion of human rights in Nepal. As a constitutional body, NHRC has the key role in the effective protection of the rights of the people which are safeguarded by the constitution and scattered laws. Article 249 of the Constitution of Nepal 2015 has clearly mentioned that it is the duty of the National Human Rights Commission to ensure the respect, protection, and promotion of human rights and its effective implementation. National Human Rights Commission Act, 2012 provides authority to NHRC to protect and promote human rights through inquiries and investigations based on the complaint lodged to the commission by the victim or any person on his/her behalf or upon information received from any source or on its own initiative. Despite the formulation of laws related to human rights, the implementation side is complicated. Use of children in the election, discrimination, labor exploitation of foreign migrant workers, and cases of domestic violence are increasing and the condition of earthquake survivors and the corona pandemic is more pathetic. Thus, the article argues that impunity still persists and the NHRC recommendations have not been implemented and it has not been able to work as per the constitutional mandate. The finding of the study is human rights situation of Nepal is still worrying. The analysis is significant as it helps to understand the human rights situation in Nepal and the functional role played by NHRC to protect human rights as the constitutional commission.